2006
DOI: 10.1002/ar.a.20323
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in digit length ratios in two lizard species

Abstract: Sexual dimorphism in digit length ratios has been reported for humans, a few other mammals, and two bird species. This dimorphism is thought to arise via an interaction between the prenatal exposure of the embryo to sex hormones and the Hox genes, which are highly conserved among vertebrates and control the development of both the appendices, including fingers and toes, and the urogenital system. In this study, we report on sexual dimorphism in 2D:3D, 2D:4D, and 3D:4D contralateral ratios of the forelimbs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
70
3
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 43 publications
9
70
3
7
Order By: Relevance
“…Evidence for directional asymmetry in the digit ratio has also been shown in mice, where a lower digit ratio in right compared with left limbs was observed (Brown et al, 2002a). In other studies, differences between digit ratios in right and left limbs have been observed, but such evidence is limited (Chang et al, 2008;Rubolini et al, 2006).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Evidence for directional asymmetry in the digit ratio has also been shown in mice, where a lower digit ratio in right compared with left limbs was observed (Brown et al, 2002a). In other studies, differences between digit ratios in right and left limbs have been observed, but such evidence is limited (Chang et al, 2008;Rubolini et al, 2006).…”
Section: Introductionmentioning
confidence: 82%
“…In all studies on digit ratio in reptiles and amphibians, where differences between sexes were significant (Chang et al, 2008, Rubolini et al, 2006Chang, 2006;Penuela, 2011;Direnzo and Stynoski, 2012), males have a higher 2D:4D, except in the back limbs of Anolis humilis, where females have a higher 2D:4D (Direnzo and Stynoski, 2012). However, newt species have the same digit ratio pattern and chromosomal sexdetermination system as mammals (Schmid et al, 1979;Hillis and Green, 1990;Sessions, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La única excepción aparece en babuinos de Guinea, en los cuales 2D/4D es mas grande en machos que en hembras (Roney et al, 2004). En aves diápsidas y reptiles, la proporción 2D/4D es generalmente mayor en machos que en hembras (Burley & Foster, 2004), lagartos de pared (Rubolini et al, 2006), y Lagartos Anolis verdes (Chang et al, 2008), siguen este patrón. Sin embargo, las lagartijas arbóreas como Mabuya planifrons no muestran dimorfismo sexual en 2D/4D (Rubolini et al, 2006).…”
Section: Introductionunclassified
“…En aves diápsidas y reptiles, la proporción 2D/4D es generalmente mayor en machos que en hembras (Burley & Foster, 2004), lagartos de pared (Rubolini et al, 2006), y Lagartos Anolis verdes (Chang et al, 2008), siguen este patrón. Sin embargo, las lagartijas arbóreas como Mabuya planifrons no muestran dimorfismo sexual en 2D/4D (Rubolini et al, 2006). Los diápsidos, reptiles y aves, tienen típicamente la proporción 2D/4D en machos más grande que en la hembra, aunque algunas excepciones pueden existir (Chang, 2008).…”
Section: Introductionunclassified